(untitled) (SAARC Journal of Agriculture, 2023)
The present study was conducted to assess the laying performances and compare the performances of three native chicken genotypes under intensive management. Egg production was recorded up to 280 days. For Kadaknath (K), a total of 500 pedigree hatched day old chicks were identified individually by wing band. In seventh generation, 26.19%, 10.89% and 18.18% birds of Non-descript Deshi (ND), Hilly (HI) and Naked Neck (NN) had laid egg ranged 80-89%. Chick weight was not affected (p>0.05) by genotype. Fertility of ND, HI and NN was 88.96%, 87.03% and 86.67%, respectively. Significantly (p<0.001) the highest hatchability (90.85%) was found in ND compared to HI (89.25%) and NN (83.94%). The highest egg production number of ND, HI and NN were 79.08, 69.33 and 74.86, respectively. In this study, the average HDEP% of ND, HI and NN were found to be 56.48, 49.52 and 53.47, respectively. Body weight at first lay is 1111.0g and at 8th week is 685.4g. FCR at 0-8 week is 3.0. Significantly (p<0.05) the lowest glucose content was found in K chicken (4.34mMol/L) compared to HI (7.34mMol/L)), NN (5.88mMol/L) and ND (5.76mMol/L). Iron content of blood was non-significantly highest in K chicken compared to other three native chickens. Haemoglobin content of blood was non-significantly highest in HI chicken. ND was superior for egg production, fertility and hatchability traits. No extra ordinary result was found in case of Kadaknath chicken. SAARC J. Agric., 21(2): 207-216 (2023)